Asesemen Ujian Nasional Dari Masa Ke Masa Dan Solusinya: Indonesia - Lutviyana Hidayah (Sekolah Tinggi Ilmu Tarbiyah Al- Kifayah Riau, 2020)
This study aims to analyze the forms of the National Examination assessment from 2005 to 2020 and see the solutions applied to suit the assessment objectives and be able to improve the quality of education. This type of research is literature research with a historical approach. The data were collected by document study and analyzed by using descriptive analysis technique. The result of this research is that the National Examination evaluation system from time to time always changes. The passing criteria are more flexible coupled with an increase in the passing percentage. This increase has resulted in the output of graduates which is often the subject of debate regarding quality or quantity. The last policy is related to the policy of eliminating the National Examination and the plan is to change it to the Minimum Competency Assessment and Character Survey which is adjusted to PISA and TIMSS. National Examination as a learning evaluation tool should be used to equalize the quality of education. Therefore, the National Examination should not only pay attention to standardization of results but also need to be balanced with standardization of processes and standardization of the process of needing to be accompanied by standardization of inputs.